High residual platelet reactivity during dual antiplatelet therapy, found by optical aggregometry and the rate of atherothrombotic complications after coronary artery stenting in patients with ischemic heart disease in clinical practice - N. F. Puchinyan; N. V. Furman; P. V. Dolotovskaya; L. L. Malinova (Столичная издательская компания, 2016)
Aim. To study the prevalence of high residual platelet reactivity (HRPR) during the dual antiplatelet therapy (DAT) with acetylsalicylic acid (ASA) and clopidogrel by optical aggregometry in patients with ischemic heart disease (IHD) after percutaneous transluminal coronary angioplasty (PTCA) in clinical practice, as well as to determine its value for the prediction of clinical course and outcome of disease.Material and methods. Patients after PTCA and during DAT were included into the study. Evaluation of the functional activity of platelets by optical aggregometry was performed in all patients at baseline. Resistance to ASA, clopidogrel and DAT were detected. Endpoints included cases of repeated atherothrombotic events (sudden cardiac death, myocardial infarction, unstable angina, ischemic stroke, stent thrombosis). Adherence to therapy was evaluated by Morisky-Green test.Results. 97 patients were included into the final analysis. The risk of myocardial infarction or unstable angina pectoris in the ASA-resistant patients was significantly higher than this in the DAT-sensitive patients [relative risk (RR)=7.68; 95% confidence interval (CI) 2.8-20.54; p=0.045]. Maximum RR for stent thrombosis was in clopidogrel-resistant (RR=7.1; 95% CI 1.41-35.82; p=0.0485) and DAT-resistant patients (RR=12.8; 95% CI 4.5-36.38; p=0.0491), compared with patients with a sensitivity to antiplatelet therapy. DAT-resistance was associated with a higher RR of the combined endpoint, compared with the sensitivity to antiplatelet therapy (RR=10.24; 95% CI 3.96-26.5; p=0.046]), and have a tendency to association with increased risk of combined endpoint compared with isolated ASA-resistance (RR=1.3; 95% CI 0.68-2.6; p=0.081).Conclusion. HRPR during DAT is common in clinical practice in patients with ischemic heart disease after PTCA. Routine use of optical aggregometry in DAT may help to identify patients with an increased risk of thrombotic events in the postoperative period and to assign them an alternative antiplatelet therapy.